Improvement of Medical Education in Developing Countries Through Best Practices (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Improvement of quantitative and qualitative dimensions of medical education is essential to provide quality health care. Research showed that medical students are facing challenges and barriers in building capacity in patient-centered health care. The study was conducted to assess opinion on factors influencing the optimum performance of medical students and collect their opinion on challenges and suggestions to overcome barriers of their learning. Materials and methods: This study was conducted at the Faculty of Medicine, University of Science & Technology Chittagong Bangladesh, in February 2014. Purposive sampling was done. Open ended questionnaire developed through modified Delphi technique was used to collect their responses. Students’ satisfaction status on quality of education and related factors was assessed and graded using Likert scale. Data analysis was conducted by excel. Results: Response rate was 87.71 % and gender difference was observed (M: F Ratio 1:2). Most of the students (39 out of 50) showed concern for further intervention to improve the existing learning environment in medical colleges. Sixty percent (60%) of respondents expressed their interest to join in any initiatives for capacity building. Conclusion: The findings of this study can be used to design cost effective strategies involving students to prepare rationally for a career in a field as challenging as medicine.JCMCTA 2017 ; 28 (2) : 39-45